2008
DOI: 10.1128/aem.01508-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Campylobacter jejuni Genes Contributing to Acid Adaptation by Transcriptional Profiling and Genome-Wide Mutagenesis

Abstract: In order to cause disease, the food-and waterborne pathogen Campylobacter jejuni must face the extreme acidity of the host stomach as well as cope with pH fluctuations in the intestine. In the present study, C. jejuni NCTC 11168 was grown under mildly acidic conditions mimicking those encountered in the intestine. The resulting transcriptional profiles revealed how this bacterium fine-tunes gene expression in response to acid stress. This adaptation involves the differential expression of respiratory pathways,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 94 publications
5
44
0
1
Order By: Relevance
“…Gene-specific disruption of Cj1321, Cj1322, Cj1323, Cj1324, or Cj1325/6 or the removal of the entire locus (Cj1321 to Cj1325/6) did not affect motility. This finding supports recently published data from Reid et al, who reported that the motility of a Cj1324 transposon mutant was unaffected compared to that of the wild type (45), and data from previous studies of genes involved in the ptm pathway, which have shown that mutagenesis in Cj1332 (ptmA) and Cj1331 (ptmB) does affect motility (20,62). The presence of flagella facilitated a top-down MS analysis of selected mutants to determine whether genes in the Cj1321-Cj1325/6 locus encode novel glycan modifications to flagellin in strain 11168H.…”
Section: Discussionsupporting
confidence: 83%
“…Gene-specific disruption of Cj1321, Cj1322, Cj1323, Cj1324, or Cj1325/6 or the removal of the entire locus (Cj1321 to Cj1325/6) did not affect motility. This finding supports recently published data from Reid et al, who reported that the motility of a Cj1324 transposon mutant was unaffected compared to that of the wild type (45), and data from previous studies of genes involved in the ptm pathway, which have shown that mutagenesis in Cj1332 (ptmA) and Cj1331 (ptmB) does affect motility (20,62). The presence of flagella facilitated a top-down MS analysis of selected mutants to determine whether genes in the Cj1321-Cj1325/6 locus encode novel glycan modifications to flagellin in strain 11168H.…”
Section: Discussionsupporting
confidence: 83%
“…The scavengase p20s appear important in pathogenesis (78), where nitrosative stress may be encountered. Several genes identified as up-regulated by GSNO in the present study (notably cgb and putative oxidoreductase genes Cj0414 and Cj0415) were also increased in a recent transcriptomic analysis of C. jejuni growing under mildly acidic conditions (79), but the significance of this cannot be explained at present.…”
Section: Discussionmentioning
confidence: 42%
“…Signature-tagged transposon mutagenesis has shown Campylobacter colonization in chickens to be complex and dynamic (Grant et al, 2005), and furthermore, screening of a transposon-based mutant library has identified C. jejuni genes that are related to polymyxin resistance and to acid adaptation of the pathogen (Lin et al, 2009;Reid et al, 2008). Additionally, transposon mutagenesis in a clinical isolate of C. jejuni has detected 26 mutants with a clearly reduced invasion capacity (Javed et al, 2010).…”
Section: Discussionmentioning
confidence: 99%